2008
DOI: 10.1016/j.bcmd.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell transcriptional networks

Abstract: Unregulated activation of mast cells can contribute to the pathogenesis of inflammatory and allergic diseases, including asthma, rheumatoid arthritis, inflammatory bowel disease, and multiple sclerosis (1;2). Absence of mast cells in animal models can lead to impairment in the innate immune response to parasites and bacterial infections (3)(4)(5). Aberrant clonal accumulation and proliferation of mast cells can result in a variety of diseases ranging from benign cutaneous mastocytosis to systemic mastocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…To identify the mechanism behind this alteration, we analyzed the expression of transcription factors that are important for the maturation and generation of BMMCs and Gr-1/Mac-1-positive myeloid cells, including Mitf, Gata-2, and PU.1. 22 As seen in Figure 3B, p85␣-deficient cells showed reduced expression of Mitf relative to WT cells. In contrast, increased expression of Gata-2 was observed in p85␣-deficient cells compared with controls ( Figure 3B).…”
Section: Resultsmentioning
confidence: 87%
“…To identify the mechanism behind this alteration, we analyzed the expression of transcription factors that are important for the maturation and generation of BMMCs and Gr-1/Mac-1-positive myeloid cells, including Mitf, Gata-2, and PU.1. 22 As seen in Figure 3B, p85␣-deficient cells showed reduced expression of Mitf relative to WT cells. In contrast, increased expression of Gata-2 was observed in p85␣-deficient cells compared with controls ( Figure 3B).…”
Section: Resultsmentioning
confidence: 87%
“…Under normal circumstances, MCP do not differentiate in the marrow, as indicated by the fact that the frequency of mast cell precursors (c-Kit high CD34 pos ) in this tissue remains limited (0.02%) throughout adult life [10]. Instead, MCP circulate in the blood to colonize extramedullary sites where they differentiate into tissue-restricted mast cells, each with a specifi c mast cell protease (MMCP) (for a review on mast cell-specifi c MMCP, see [11,12]) expression profi le [13,14], giving rise to dermal, mucosal, and serosal mast cell populations. The molecular mechanism in normal mice that restricts the mastocytopoietic potential of stem/progenitor cells to extramedullary sites, as well as the factors that guide their differentiation along different lineages is unknown.…”
mentioning
confidence: 99%
“…The mechanisms of this potential cooperativity between GATA-1 and PU.1 require further investigation. We have previously shown that, in fetal liver and yolk sac, the chromatin in both the IE and IB regions is open (4). Other investigators have also identified open chromatin that is sensitive to DNase I close to the IB start site in a multipotential hematopoietic progenitor cell line FDCP-mix (45).…”
Section: Discussionmentioning
confidence: 89%
“…Mature mast cells in the connective and mucosal tissues differentiate from uncommitted hematopoietic stem cells in the bone marrow; this process of lineage selection is orchestrated by a network of tightly regulated transcription factors (4). Current models of hematopoiesis suggest that multiple lineage-specific transcription factors are expressed at low levels in early, pluripotent progenitor cells.…”
mentioning
confidence: 99%